The African diaspora population in Britain migrant identities and experiences - Aspinall, Peter J. 1947-; Chinouya, Martha J. (Migration, diasporas and citizenship, 2016)
"This insightful book examines the Black African diaspora in Britain through an examination of its demography, recent patterns of migration, changing patterns of residence, and socio-economic position. It provides an analysis of the areas where Black Africans face disadvantage, including labour market participation, housing markets, health and social care, and residence in deprived neighbourhoods. This original and important research also deals with categories and identities, using data collected in the 2011 Census on national identity, and the resulting investigation of the social, cultural and civic life of Black Africans presents the substantial heterogeneity concealed in the label 'Black African', concluding by highlighting the policy implications of this vital research."...Publisher's website